2006
DOI: 10.1088/1742-6596/43/1/329
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Nonlinear Dynamics Observed in NbN Superconducting Microwave Resonators

Abstract: In this work we characterize the unusual nonlinear dynamics of the resonance response, exhibited by our NbN superconducting microwave resonators, using different operating conditions. The nonlinear dynamics, occurring at relatively low input powers (2-4 orders of magnitude lower than Nb), and which include among others, bifurcations in the resonance curve, hysteresis loops and resonance frequency shift, are measured herein using varying temperature, applied magnetic field, white noise and rapid frequency sweep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
2
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
(58 reference statements)
2
2
0
Order By: Relevance
“…For our 4 µm and 2.5 µm devices, microwave powers at the input port of the resonator beyond −15 and −23 dBm (B 1 = 0.2 and 0.09 µT), respectively, were seen to affect the resonance lineshape without bias currents. This behavior has been reported previously 21,22 , and is a signature of the strong nonlinearity of the superconductor. (2) In our DEER experiments, we applied two bias current pulses -one before, and another after the π pulse on 31 P donors -to cancel phase accumulation from the inhomogeneous magnetic fields generated by the bias currents.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…For our 4 µm and 2.5 µm devices, microwave powers at the input port of the resonator beyond −15 and −23 dBm (B 1 = 0.2 and 0.09 µT), respectively, were seen to affect the resonance lineshape without bias currents. This behavior has been reported previously 21,22 , and is a signature of the strong nonlinearity of the superconductor. (2) In our DEER experiments, we applied two bias current pulses -one before, and another after the π pulse on 31 P donors -to cancel phase accumulation from the inhomogeneous magnetic fields generated by the bias currents.…”
supporting
confidence: 84%
“…From simulations that take into account the full distribution of B i and the microwave magnetic field, B 1 , we estimate that a broadening comparable to the ESR linewidth can be caused by a misalignment of ∼ 4.7 • . Additionally, we observed that microwave powers larger than -32 dBm affected the resonance lineshape with a bias current of 4 mA due to the non-linearity of the superconductor 21,22 . The reduced signal intensity for rectangular pulses is due to a combination of reduced microwave power and broadening due to misalignment.…”
mentioning
confidence: 88%
“…Microwave powers exceeding -64 dBm were observed to distort the resonance lineshapes of some of the resonators. This behavior has been observed previously, and is a signature of the large kinetic inductance of the superconductor 19,20 . For the remainder of this work, we focus on one of the SKIFFS with nw = 10 µm and a resonance frequency near 4.2 GHz.…”
Section: Fig 1 (A)supporting
confidence: 83%
“…The merit of nonlinearity can be studied by measuring the parametric variation of the quality factor (Q-factor), the surface reactance, and the resistance of superconducting resonators. Such a variation always behaves as a function of the frequencies and power levels of the input signal [3], external magnetic field, or ambient temperature [4], [5]. The nonlinearity can even be found by measuring higher orders of harmonic power spectra [6].…”
mentioning
confidence: 99%